Human Resource Development Policy in Nepal’s Local Governments: Challenges and Reform Imperatives - Adhikari, Shiva Raj; Dhakal, Tek Nath; Ghimire, Mahesh (NPRC Journal of Multidisciplinary Research, 2026)
Background: Public sector reform and decentralization have reshaped local governance in Nepal, yet human resource development (HRD) remains a critical challenge for effective service delivery. Objectives: This study examines the effect of public sector reform on HRD policies in Nepal’s local governments, identifies capacity-related problems of public sector workers, and explores reform imperatives for strengthening decentralized governance. Methods: An exploratory case study design was employed, using surveys and in-depth interviews with 115 local government employees across metropolitan, sub-metropolitan, and municipal offices, supplemented by key informant interviews with twelve senior officials and analysis of institutional records. Data triangulation combined quantitative descriptive statistics with thematic qualitative analysis. Findings: Public sector reform has influenced HRD direction within decentralization, but multidimensional capacity problems persist: policy-based challenges (ineffective HRD systems, poor information management), skill/task/organizational problems (inadequate training funding, lack of career development, absent HR units), and performance/motivation deficits (low job satisfaction due to poor salaries, unequal training access, inadequate recognition). Metropolitan municipalities demonstrated stronger HRD relevance (mean 3.29) than smaller municipalities (2.77). Critical issues included low policy awareness (1.89) and insufficient management investment in staff development (2.02). Conclusion: HRD challenges in Nepal’s local governments are complex and interconnected, requiring systemic reforms beyond isolated training programs. Implication: Establishing professional HRD units at all local levels, aligning HRD with organizational culture and systems, and addressing salary structures and motivational factors are essential for building a competent, resilient workforce capable of delivering responsive public services through decentralized governance.